Integration into Formal Economy: A Systematic Review on the Challenges and Opportunities for Informal SMEs in Cambodia - Or, Chanthan; Phon, Sophat; Serey, Mardy (Journal of Law and Economics, 2025)
The informal economy accounts for a substantial share of economic activity across developing nations, where Small and Medium Enterprises (SMEs) serve as primary engines for job creation and income generation. Yet informality frequently confines these enterprises to persistent cycles of low productivity and economic vulnerability. Drawing on 12 studies published between 2000 and 2025, our systematic literature review examines the multifaceted barriers and pathways associated with transitioning informal SMEs into the formal economy, with particular attention to Cambodia. We synthesize theoretical frameworks on informal economy dynamics and SME development, analyze Cambodia's informal sector characteristics, identify formalization obstacles, and examine integration possibilities. Our literature search spanned multiple databases—JSTOR, Google Scholar, and repositories from the ILO, UNDP, World Bank, and ADB. We selected peer-reviewed articles and reports addressing informal economy and SME formalization in Cambodia and Southeast Asia more broadly. Our findings reveal that despite substantial barriers—financial constraints and regulatory complexities—targeted policy interventions can unlock considerable integration potential.